2015
DOI: 10.1002/pros.23105
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane prostatic acid phosphatase (TMPAP) delays cells in G1 phase of the cell cycle

Abstract: Our data suggests that TMPAP may function as a non-canonical tumor suppressor by delaying cell growth in G1 phase of the cell cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…PAP is a phosphotyrosyl-protein phosphatase [35] with multiple phosphomonoester substrates that functions at an optimum pH range of 4.0 to 6.0 [36]. There are two different isoforms of PAP that result from alternate splicing of the same gene product: (i) a secreted isoform and (ii) a transmembrane isoform [37]. The secreted enzyme PAP is a glycoprotein, nonspecific tyrosine phosphatase, constituted in its active form as a 100-kDa dimer composed of two subunits of 50 kDa [38].…”
Section: The Role Of Pap In Osteoblastic Bone Metastasesmentioning
confidence: 99%
“…PAP is a phosphotyrosyl-protein phosphatase [35] with multiple phosphomonoester substrates that functions at an optimum pH range of 4.0 to 6.0 [36]. There are two different isoforms of PAP that result from alternate splicing of the same gene product: (i) a secreted isoform and (ii) a transmembrane isoform [37]. The secreted enzyme PAP is a glycoprotein, nonspecific tyrosine phosphatase, constituted in its active form as a 100-kDa dimer composed of two subunits of 50 kDa [38].…”
Section: The Role Of Pap In Osteoblastic Bone Metastasesmentioning
confidence: 99%
“…PAcP) is a prostatespecific acid phosphatase with a critical role PCa etiology and has been suggested as a PCa biomarker long before PSA [43]. ACP3 is known to inhibit cell proliferation and is therefore typically down-regulated in PCa [44], despite elevated ACP3 protein levels in patient blood [43]. In our cohort ACP3 levels were strongly down-regulated in all of the high-grade patients and in the vast majority of low-and intermediate-grade patients, suggesting that ACP3 down-regulation represents an early event during PCa evolution.…”
Section: Effects Of Distinct Cnas Converge On Common Proteinsmentioning
confidence: 99%
“…Some studies have indicated that the growth regulatory form of PAcP appears to be the secretory one and that this PAcP isoform positively regulates prostatic epithelial cell growth . In contrast, tPAcP negatively regulates prostate cancer cell growth . Interestingly, development of the prostate gland from birth through sexual maturity in the human male is mirrored by changes in cPAcP expression.…”
Section: Introductionmentioning
confidence: 99%